2020
DOI: 10.1128/aac.00668-20
|View full text |Cite
|
Sign up to set email alerts
|

Radial Expansion Facilitates the Maintenance of Double Antibiotic Resistances

Abstract: Most microbes live in spatially confined sub-populations. Under spatial structure, the efficacy of natural selection is often reduced (relative to homogeneous conditions), due to the increased importance of genetic drift and local competition. Additionally, under spatial structure, the fittest genotype may not always be the one with better access to the heterogeneous distribution of nutrients. The effect of radial expansion may be particularly relevant for the elimination of antibiotic resistance mutations, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The hypothesis that STR resistance can predispose to resistance to other drugs has been raised in different studies [ 19 , 37 , 38 , 90 ]. Research with Escherichia coli showed evidence pointing to a beneficial role in the combination of mutations associated with resistance to STR and RIF [ 91 , 92 ]. In these studies, it was shown that double-resistant STR and RIF E. coli can compensate for the fitness cost of drug resistance mutations faster than single-resistant bacteria [ 91 , 92 ].…”
Section: Streptomycin-resistant Mutations and Fitness Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that STR resistance can predispose to resistance to other drugs has been raised in different studies [ 19 , 37 , 38 , 90 ]. Research with Escherichia coli showed evidence pointing to a beneficial role in the combination of mutations associated with resistance to STR and RIF [ 91 , 92 ]. In these studies, it was shown that double-resistant STR and RIF E. coli can compensate for the fitness cost of drug resistance mutations faster than single-resistant bacteria [ 91 , 92 ].…”
Section: Streptomycin-resistant Mutations and Fitness Costsmentioning
confidence: 99%
“…Research with Escherichia coli showed evidence pointing to a beneficial role in the combination of mutations associated with resistance to STR and RIF [ 91 , 92 ]. In these studies, it was shown that double-resistant STR and RIF E. coli can compensate for the fitness cost of drug resistance mutations faster than single-resistant bacteria [ 91 , 92 ]. Interestingly, attention has been called to the fact that the STR resistant bacterial populations are more likely to have mutations that compensate for fitness costs than RIF resistant ones [ 92 ].…”
Section: Streptomycin-resistant Mutations and Fitness Costsmentioning
confidence: 99%
“…Recent in vitro work in E. coli shows that reduced competition due to spatial segregation may allow for the maintenance of multiple AMR mutations for longer durations compared to populations without spatial segregation (Durão et al . 2020 ). Thus, for the MTBC, low between-lesion migration levels would hypothetically lead to higher levels of MTBC genetic diversity and, consequently, higher likelihood of heteroresistance observed within TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…environmental, and medical purposes. However, predicting how complex communities of microbes behave over large timescales is difficult since competition for scarce resources and limited space among diverse strains and species can be complex (Durão et al, 2020;Estrela & Brown, 2018;Ghoul & Mitri, 2016;Goldford et al, 2018;Hibbing et al, 2010;Pande & Kost, 2017;Pande et al, 2014).…”
mentioning
confidence: 99%